COMPLIANCE ASSESSMENT IN PATIENTS WITH EPILEPSY IN SMOLENSK REGION - N. N. Maslova; N. V. Yurieva (Эпилепсия и пароксизмальные состояния, 2016)
The purpose of epilepsy treatment is complete termination of seizures or maximum reduction of their number with minimal side effects from treatment. One of the reasons of treatment failure is low patient compliance. The objective of our study was the analysis of compliance of patients with epilepsy in the Smolensk region, depending on patient’s age. Objective: the analysis of compliance of patients with epilepsy in the Smolensk region, depending on the age of the patient.Materials and methods: a selected group of patients, where there is used or counting the remaining pills, questioning patients and their relatives, check diaries episodes and the diary of taking AEDs.Results: the patient groups with the highest and lowest compliance.Conclusion: the failure of drug-free remission, when clicking on some analogues caused the violation of the therapeutic interaction doctor — patient in all age groups.